Nylon composite material as well as preparation method and application thereof

By adding boehmite and hydrotalc to the nylon composite material and using the compatibility differences of PET resin to form a separator, the corrosion problem of halogen-free organic phosphine-based flame-retardant nylon materials on silica under high temperature conditions is solved, and the high CTI value and UL94 V0 flame retardant grade is achieved. It is suitable for new energy high-voltage connectors and energy storage connectors.

CN119684787AActive Publication Date: 2025-03-25SHANGHAI KINGFA SCI & TECH +1

Patent Information

Application Number
CN202411727082.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-25
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing halogen-free organic phosphine-based flame-retardant nylon materials are corrosive to silicone under high temperature conditions, affecting the sealing and service life of the product.

Method used

By adding boehmite to the nylon composite material as a synergistic flame retardant, and combining the acid absorption properties of hydrotalcite and the compatibility differences between PET resin, a layer of separator is formed to reduce the migration of organophosphorus flame retardant to the surface layer and reduce corrosion to silica gel.

Benefits of technology

It realizes the corrosion resistance of nylon composite materials to silicone under high temperature conditions, while maintaining high CTI value and UL94 V0 flame retardant grade, and is suitable for new energy high-voltage connectors and energy storage connectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the field of halogen-free organic phosphine flame-retardant nylon, and particularly relates to a nylon composite material as well as a preparation method and application thereof. Specifically, the nylon composite material disclosed by the invention comprises the following components in parts by weight: 65-82 parts of polyamide resin; 12 to 18 parts of a hypophosphite flame retardant; 10 to 50 parts of a reinforcing agent; 0.5 to 2 parts of hydrotalcite; 3 to 8 parts of boehmite; and 1-3 parts of PET resin. The organic phosphine flame-retardant nylon composite material provided by the invention solves the problem of corrosivity of an organic phosphine flame-retardant nylon material to silica gel under a high-temperature condition, and is resistant to silica gel corrosion under the high-temperature condition, high in CTI value and capable of meeting the UL94 V0 flame-retardant grade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of halogen-free organic phosphine flame-retardant nylon, and particularly relates to a nylon composite material and a preparation method and application thereof. Background Art

[0002] Polyamide resin has excellent comprehensive properties such as mechanical properties, barrier properties, heat resistance, wear resistance, and chemical corrosion resistance. Its composite materials are widely used in machinery manufacturing, industrial connectors, power tools, electronic appliances, transportation and other fields.

[0003] Among its many application scenarios, nylon is increasingly used in new energy high-voltage connector products. Energy storage connector products are part of new energy high-voltage connector products and have very high material requirements: 1. High IPT characteristics. According to the provisions of UL4128-Outline of inter-cell and inter-layer connectors for electrochemical battery systems, when the rated voltage is 600V~2000V and the creepage distance between electrodes is less than 16mm, the IPT performance of the test material is required. There are many material solutions with IPT≤1.0KV, but there are very few materials with IPT≥1.5KV.

[0004] 2. High RTI value requirements. The higher the RTI value, the better the long-term high temperature resistance of the material and the longer the service life of the material. As the current carried by the energy storage connector product increases, the heat generated increases, and higher requirements are placed on the long-term heat resistance of the material.

[0005] 3. Resistance to silicone corrosion. Energy storage connector products are located in unattended environments for a long time, so they have strict protection and sealing requirements for harsh environments such as high humidity and high dust. Silicone rubber, a sealing material, will be used. However, some flame retardant materials are easy to corrode silicone due to their strong acidity. Especially in high temperature environment for a long time, silicone corrosion is serious, affecting the sealing of the product and easily causing product failure.

[0006] 4. Highly flame retardant, all colors meet the UL94 V0 flame retardant requirements. Energy storage connector products work with power for a long time, which has higher requirements for electrical safety. The materials must meet the UL94 V0 flame retardant requirements.

[0007] Among many flame retardant systems, halogen-free organic phosphine flame retardant has many advantages such as low smoke and halogen-free, high flame retardant efficiency, high CTI, color matching, good mechanical properties, etc., and is widely used in the field of new energy connectors. However, in the existing technology, organic phosphine flame retardant nylon materials have not proposed an effective solution to the problem of corrosion of silicone under high temperature conditions, which has an adverse effect on the application and promotion of new energy high-voltage connector products. Summary of the invention

[0008] The object of the present invention is to solve the above technical problems and provide a nylon composite material which is resistant to silicone corrosion under high temperature conditions, has a high CTI value, and meets the UL94 V0 flame retardant grade.

[0009] Another object of the present invention is to provide a method for preparing the above nylon composite material.

[0010] Another object of the present invention is to provide applications of the above nylon composite material.

[0011] The present invention is achieved through the following technical solutions: A nylon composite material, comprising the following components in parts by weight: 65-82 parts of polyamide resin; 12-18 parts of hypophosphite flame retardant; Enhancer 10-50 parts; 0.5-2 parts of hydrotalcite; 3-8 parts of boehmite; 1-3 parts of PET resin.

[0012] Preferably, the mineral modifier is selected from a compound of hydrotalcite and boehmite, and the weight ratio of hydrotalcite:boehmite is 1:(4-7).

[0013] The D50 particle size range of hydrotalcite is 0.1μm to 0.8μm. The D50 particle size test method is to place 1g of hydrotalcite in 500ml of ethanol solution, disperse it by ultrasonic vibration for 5 minutes, shake it well, and then take the suspension into the Darwin particle size analyzer to obtain the D50 value.

[0014] Preferably, the polyamide resin is selected from any one or more of PA66, PA610, PA612, PA1012, PA46, MXD6, PA6, PA7, PA11, PA12, PA6T or PA66 / 6T; More preferably, any one or more of PA6, PA66 or PA66 / 6T; More preferably, it is PA66 / 6T.

[0015] In the nylon composite material of the present invention, the polyamide resin preferably accounts for 40-78wt% of the total weight.

[0016] Preferably, the mass percentage of terephthalic acid monomer units in the PA66 / 6T resin is 22%-28%.

[0017] Preferably, the hypophosphite flame retardant is selected from diethyl aluminum hypophosphite.

[0018] Preferably, the reinforcing agent is selected from any one or more of glass fiber or mineral filler; more preferably, it is glass fiber.

[0019] Preferably, the glass fiber is selected from any one or more of chopped strand A-, E-, C-, D-, S- and R-glass fibers; and the cross-section of the glass fiber is circular or non-circular.

[0020] The diameter of the glass fiber is in the range of 6 μm to 15 μm, and the length is in the range of 1.0 mm to 10 mm.

[0021] Preferably, the D50 particle size of the boehmite is 0.1-2.5 microns, and more preferably 0.5-0.8 microns. The D50 particle size test method is to place 1g of boehmite in 500ml of ethanol solution, disperse it by ultrasonic vibration for 5 minutes, shake it well, and then take the suspension into the Darwin particle size analyzer to obtain the D50 value.

[0022] Preferably, the intrinsic viscosity of the polyethylene terephthalate resin is 0.6-1.1 dl / g, more preferably 0.65-0.88 dl / g, and the test standard is ISO 1628-1.

[0023] The present invention provides a method for preparing the above-mentioned nylon composite material, comprising the following steps: according to a ratio, each component except a reinforcing agent is uniformly mixed, added from a feeding port of a first section of a twin-screw extruder, the reinforcing agent is added from a fifth section of the screw barrel, and then melt extrusion granulation is performed, the corresponding screw barrel temperatures of the extruder are 80°C, 240°C, 270°C, 270°C, 250°C, 240°C, 240°C, 240°C, 250°C and 270°C, respectively, the screw speed range is 300rpm-500rpm, and the nylon composite material is obtained after cooling and pelletizing.

[0024] The present invention provides an application of the above-mentioned nylon composite material for preparing energy storage connector components.

[0025] The present invention has the following beneficial effects: Organic phosphine flame retardant materials will corrode silicone under high temperature conditions. Since diethylphosphinate itself is highly acidic with a pH value of 3.0-5.0, the acidity is even stronger under high temperature conditions. It is easily decomposed into phosphates and diethylphosphinate and other acidic substances when heated, which react with the Si-O bonds of silicone rubber, causing them to crack and break the chains, causing permanent deformation of the silicone, thereby affecting the sealing of the product. However, this process does not occur at room temperature, so the problem of silicone corrosion will only occur in specific environments.

[0026] The present invention uses boehmite as a synergistic flame retardant, and does not introduce MPP which is beneficial to flame retardancy. The main reason is that MPP has strong acidity and is easy to migrate to the surface of the sample, which will accelerate the corrosion of silica gel. Secondly, hydrotalcite, a layered silicate, is introduced, which has strong acid absorption and can reduce the acidity of the system and reduce the high-temperature degradation reaction of acidic substances to silica gel. Finally, a small amount of PET resin is introduced, which has poor compatibility with nylon and will be enriched on the surface of the product during the injection molding process, similar to forming a diaphragm, reducing the migration of the organic phosphorus flame retardant to the surface, and further weakening the interaction between the flame retardant and silica gel.

[0027] Through the combined effect of these factors, the use of composite materials has excellent silicone corrosion properties, while not affecting the high CTI properties and flame retardant grade, making it have very good application prospects in new energy high-voltage connectors, especially energy storage connectors.

[0028] The scheme of the present invention has high feasibility and effectiveness, and is simple and effective to operate. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0030] The raw materials used in the present invention come from: Nylon 66: PA66 EP-158, Huafeng Group Co., Ltd.

[0031] Nylon 6: PA6 HY-2500A, Haiyang Technology Co., Ltd.

[0032] Nylon 66 / 6T: NPD-652, INVISTA (China) Investment Co., Ltd.

[0033] Nylon 1012: PA1012 RV26, Cangzhou Lingang Anaiji New Materials Co., Ltd.

[0034] MXD6: PA MXD6 M30L, Shanghai Yinggu Chemical Co., Ltd.

[0035] Nylon 12: VESTAMID L1940 NC, Evonik Industries AG.

[0036] Diethylaluminum hypophosphite: OP 1230, Clariant Chemicals Co., Ltd.

[0037] Wollastonite: HQ-1250, Dalian Global Minerals Co., Ltd.

[0038] Glass fiber: ECS10-03-568H, China Jushi Co., Ltd.

[0039] Hydrotalcite 1: AC-320, D50 particle size is 0.1 μm, produced by Chenghe Technology.

[0040] Hydrotalcite 2: DHT-4A, D50 particle size: 0.4 μm, produced by Kyowa Chemical Industry Co., Ltd.

[0041] Hydrotalcite 3: FM300 FM803, D50 particle size is 0.8 μm, Kanggaote New Material Technology Co., Ltd.

[0042] Boehmite 1: BG-613SO, D50 particle size: 1.75 μm, Anhui Yishitong Material Technology Co., Ltd.

[0043] Boehmite 2: LSB-2-2, D50 particle size: 0.65 μm, China Aluminum Zhengzhou Nonferrous Metals Research Institute Co., Ltd.

[0044] Boehmite 3: B8014-LM, D50 particle size 0.15 μm, Tianjin Boyuan High-tech Materials Co., Ltd.

[0045] PET resin 1: polyethylene terephthalate resin, model PET BG80, relative density 1.34, intrinsic viscosity 0.80 dl / g, purchased from Yizheng Branch of Sinopec Asset Management Co., Ltd.

[0046] PET resin 2: polyethylene terephthalate resin, model PET SY-G105, relative density 1.34, intrinsic viscosity 1.09 dl / g, purchased from Wujiang Shuangyang Polyester Modification Factory.

[0047] PET resin 3: polyethylene terephthalate resin, model PET CR-7702, relative density 1.31, intrinsic viscosity 0.50 dl / g, purchased from China Resources Packaging Materials Co., Ltd.

[0048] Various test methods: (1) Evaluation of silicone corrosion: Injection mold a 60*60*3.0mm square plate, place a circular silicone ring with a diameter of 10mm and a thickness of 4mm flat in the middle of the square plate, and then cover the square plate. Keep the silicone ring in place, then place a 200g weight in the middle of the upper cover, and then put the entire device into a 120℃ oven for 672h. Finally, record the thickness of the silicone ring and calculate the height change rate of the silicone ring. The greater the change rate, the more permanent deformation of the silicone will occur, and the more serious the corrosion of the material to the silicone will be.

[0049] (2) CTI of plastic raw materials: tested according to GB / T4207-2012, sample size: 60mm*60mm*3.0mm, CTI test range is (0~1000)V.

[0050] (3) Flame retardant grade test: refer to UL 94 standard, the test specimen size is 125mm*13mm*1.6mm.

[0051] Table 1 Weight parts of each component and test results of nylon composite materials of Examples 1-9

[0052] Table 2 Weight parts of each component and test results of nylon composite materials of Examples 10-18

[0053] It can be seen from Examples 3-9 that, when other components and conditions are the same, the use of nylon 66 / 6T can reduce the corrosion resistance of silicone to 5.80%, increase the tracking index to 750V, and at the same time meet the flame retardant grade of V-0.

[0054] It can be seen from Example 5 and Example 10 that, when other components and conditions are the same, using glass fiber as a reinforcing agent has a better effect on silicone corrosion and tracking index than using mineral fillers.

[0055] It can be seen from Example 5 and Examples 11-12 that, when other components and conditions are the same, selecting a hydrotalcite D50 with a particle size range of 0.3-0.5 μm has a better effect.

[0056] It can be seen from Example 5 and Examples 13-14 that, when other components and conditions are the same, the boehmite particle size of 0.5-0.8 μm has better performance in the silica gel corrosion and tracking index tests.

[0057] It can be seen from Example 5 and Examples 15-16 that, when other components and conditions are the same, the intrinsic viscosity of the PET resin is preferably 0.6-1.1 dl / g, and more preferably 0.65-0.88 dl / g.

[0058] It can be seen from Example 5 and Examples 17-18 that, when other components and conditions are the same, adding an excessive amount of hydrotalcite or boehmite will improve the corrosion resistance of silica gel while reducing the tracking index to 600V.

[0059] Table 3 Weight parts of each component and test results of nylon composite materials of Comparative Examples 1-4

[0060] It can be seen from Comparative Example 1 that the absence of hydrotalcite has a significant impact on the corrosiveness of silica gel.

[0061] It can be seen from Comparative Example 2 that the failure to add boehmite increases the silicone corrosion of the nylon composite material, reduces the tracking index, and the flame retardant grade cannot reach V-0.

[0062] It can be seen from Comparative Example 3 that the failure to add PET resin results in an increase in the corrosiveness of the silica gel.

[0063] It can be seen from Comparative Example 4 that adding an excessive amount of PET resin has a greater impact on the tracking index, and the tracking index drops to 500V.

Claims

1. A nylon composite material, characterized in that: According to weight parts, it contains the following ingredients: 65-82 parts of polyamide resin; 12-18 parts of hypophosphite flame retardant; Enhancer 10-50 parts; 0.5-2 parts of hydrotalcite; 3-8 parts of boehmite; 1-3 parts of PET resin.

2. A nylon composite material according to claim 1, characterized in that: The polyamide resin is selected from any one or more of PA66, PA610, PA612, PA1012, PA46, MXD6, PA6, PA7, PA11, PA12, PA6T or PA66 / 6T; preferably any one or more of PA6, PA66 or PA66 / 6T; more preferably PA66 / 6T.

3. A nylon composite material according to claim 1, characterized in that: The hypophosphite flame retardant is selected from diethyl aluminum hypophosphite.

4. A nylon composite material according to claim 1, characterized in that: The reinforcing agent is selected from any one or more of glass fiber or mineral filler, and is preferably glass fiber.

5. A nylon composite material according to claim 4, characterized in that: The glass fiber is selected from any one or more of chopped strand A-, E-, C-, D-, S- and R-glass fibers; the cross section of the glass fiber is circular or non-circular.

6. The nylon composite material according to claim 1, characterized in that: The D50 particle size of the boehmite is 0.1-2.5 microns, preferably 0.5-0.8 microns.

7. The nylon composite material according to claim 1, characterized in that: The intrinsic viscosity of the polyethylene terephthalate resin is 0.6-1.1 dl / g, preferably 0.65-0.88 dl / g.

8. The method for preparing a nylon composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: according to a proportion, each component except a reinforcing agent is uniformly mixed, and the components are added from a feeding port of a first section of a twin-screw extruder, and the reinforcing agent is added from a fifth section of a screw barrel, and then melt extrusion granulation is performed, the corresponding screw barrel temperatures of the extruder are 80°C, 240°C, 270°C, 270°C, 250°C, 240°C, 240°C, 240°C, 250°C and 270°C, respectively, the screw speed range is 300rpm to 500rpm, and the nylon composite material is obtained after cooling and pelletizing.

9. The use of a nylon composite material according to any one of claims 1 to 7, characterized in that: Used to prepare energy storage connector components.

Citation Information

Patent Citations

  • Flame-retardant resin composition

    CN103328583A

  • Dialkyl phosphinic acid-aluminum phosphite composite salt and preparation method and application thereof

    CN112876736A

Cited By

  • Nylon composite material, and preparation method therefor and use thereof

    WO2026114110A1